Principles for socially inclusive digital tools for smallholder farmers: A guide. Version 2 - Dittmer, Kyle M; Burns, Sessie; Shelton, Sadie; Wollenberg, Eva (2024)
This guide addresses concerns with the current digitalization of food systems by providing principles for developing socially inclusive digital tools with smallholder farmers. These principles aim to increase social and livelihood benefits for diverse and underrepresented farmers. Co-creation of farm practices with farmers is emphasized as a key element of social inclusion, ensuring relevance to farmers’ livelihoods and robust technical solutions. The principles support digital developers and managers using digital tools with farmers and help funders, farmers’ organizations, or NGOs hold developers accountable to social inclusion principles.